High-ambition climate action in all sectors can achieve a 65% greenhouse gas emissions reduction in the United States by 2035 - Alicia Zhao; Kowan T. V. O’Keefe; Matthew Binsted; Haewon McJeon; Adriana Bryant; Claire Squire; Mengqi Zhang; Steven J. Smith; Ryna Cui; Yang Ou; Gokul Iyer; Shannon Kennedy; et al. (npj Climate Action, 2024)
Abstract Under the next cycle of target setting under the Paris Agreement, countries will be updating and submitting new nationally determined contributions (NDCs) over the coming year. To this end, there is a growing need for the United States to assess potential pathways toward a new, maximally ambitious 2035 NDC. In this study, we use an integrated assessment model with state-level detail to model existing policies from both federal and non-federal actors, including the Inflation Reduction Act, Bipartisan Infrastructure Law, and key state policies, across all sectors and gases. Additionally, we develop a high-ambition scenario, which includes new and enhanced policies from these actors. We find that existing policies can reduce net greenhouse gas (GHG) emissions by 44% (with a range of 37% to 52%) by 2035, relative to 2005 levels. The high-ambition scenario can deliver net GHG reductions up to 65% (with a range of 59% to 71%) by 2035 under accelerated implementation of federal regulations and investments, as well as state policies such as renewable portfolio standards, EV sales targets, and zero-emission appliance standards. This level of reductions would provide a basis for continued progress toward the country’s 2050 net-zero emissions goal.